2018
DOI: 10.1007/s12032-018-1101-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety of long-term anticoagulation in patients with brain metastases

Abstract: Anticoagulation is thought to be associated with the risk of intracranial hemorrhage (ICH) in patients with brain metastases; however, the data on this topic are limited. This study was conducted to determine the incidence of ICH associated with anticoagulant use in adult patients with brain metastases. Consecutive patients with brain metastases occurring from 2006 to 2014 were identified from a single-institution database. Long-term anticoagulant therapy was defined as outpatient anticoagulation therapy of > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The authors found the highest rate of ICH in the patients undergoing WBRT and SRS as opposed to other treatments for BM [36]. The overall low incidence of bleeding events prevented the observation of any statistically significant findings [36]. Our results are supported by the data of Horstmann et al, with comparable frequencies of bleeding events [36].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The authors found the highest rate of ICH in the patients undergoing WBRT and SRS as opposed to other treatments for BM [36]. The overall low incidence of bleeding events prevented the observation of any statistically significant findings [36]. Our results are supported by the data of Horstmann et al, with comparable frequencies of bleeding events [36].…”
Section: Discussionsupporting
confidence: 84%
“…Approximately 50% of these patients suffered from primary non-small-cell lung cancer (NSCLC), and a total of twelve ICHs occurred. Of these twelve bleeding events, eight occurred in patients with ACT, and this equated to a non-significant increase compared to the number of events in patients without ACT [36]. The authors found the highest rate of ICH in the patients undergoing WBRT and SRS as opposed to other treatments for BM [36].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations